Sedimentary Architecture of Storm-Influenced Tidal Flat Deposits of the Upper Mulichinco Formation, Neuquén Basin, Argentina - Sleveland, Arve R. N.; Midtkandal, Ivar; Galland, Olivier; Leanza, Héctor A. (Frontiers in Earth Science, 2020)
This study reports on the Lower Cretaceous upper Mulichinco Formation in the Neuquén Basin, west-central Argentina. The studied succession comprises shallow marine strata, deposited in a mixed wave and tidal flat environment where ebb-tidal currents dominated. We describe mixed storm- and tide-influenced deposits within progradationally stacked high-frequency sequences, and discuss process interaction, sediment dispersal and preservation potential. These storm and tidal deposits mix spatially on bed-, bedset- and sequence scales, suggesting multiscale process interaction. The study investigates a 12 km long continuous outcrop, oriented sub-parallel to the paleocoastline. The succession comprises subtidal flat and meandering tidal channel complexes, with interbedding and interfingering of storm and tidal deposits. The tidal deposits are widespread and comprise moderately sorted sandstones with bimodal paleocurrent directions, single and double mud drapes, reactivation surfaces, and inclined heterolithic stratification. Varying bimodal paleocurrent directions suggest that the paleocoastline was irregular, consisting of both protrusions and bays. Storm deposits are mainly found erosively interbedded with subtidal flat sandstones, and exhibit dm-thick well sorted hummocky and swaley cross-stratified sandstones. These storm deposits show systematic lateral variations in abundance, from dominant to absent, which is linked to subtle variations in water depth along the irregular paleocoastline. As the tidal deposits are widespread across the study area, and with no significant facies change, the varying dispersal of storm-influenced deposits is considered a product of wave refraction, with converging and diverging wave energy at interpreted positions of coastal protrusions and embayments, respectively. Consequently, the irregular paleocoastline morphology caused spatial variability in wave impact and controlled preservation of interbedded storm and tidal deposits at the coastal protrusions, while facilitating complete tidal remobilization of sediments in the embayments. With no evidence for fluvial influence, ebb-tidal currents are considered as the main drivers for sediment dispersal onto the subtidal flat, through the meandering tidal channels.